A Hybrid Approach for the Synthesis of Nonuniformly Spaced and Excited Linear Arrays With Strict Element Spacing Constraints - Yang, Jianhua; Yang, Peng; Yang, Feng; Xing, Zhiyu (IEEE transactions on antennas and propagation, 2022)
A hybrid methodology for the synthesis of nonuniformly spaced and excited linear arrays is proposed. At first, a modified genetic algorithm (GA) named linear-constraint genetic algorithm (LCGA) is discussed in this article to adapt to generalized linear-constraint optimization problems. Then, by nesting the technique of convex programming (CP) into LCGA, a hybrid optimization implementation is developed to jointly optimize the position and excitation variables. Due to the linear-constraint character of LCGA, array layouts can be exactly constrained with element spacings and the aperture size. A set of representative numerical experiments shows the effectiveness of this method to obtain very high-quality solutions.